2022
DOI: 10.1038/s42003-022-04339-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil trafficking to the site of infection requires Cpt1a-dependent fatty acid β-oxidation

Abstract: Cellular metabolism influences immune cell function, with mitochondrial fatty acid β-oxidation and oxidative phosphorylation required for multiple immune cell phenotypes. Carnitine palmitoyltransferase 1a (Cpt1a) is considered the rate-limiting enzyme for mitochondrial metabolism of long-chain fatty acids, and Cpt1a deficiency is associated with infant mortality and infection risk. This study was undertaken to test the hypothesis that impairment in Cpt1a-dependent fatty acid oxidation results in increased susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that inhibiting fatty acid metabolism in neutrophils through CPT1a mediates an impact on neutrophil chemotaxis [39]. To investigate whether the inhibition of CPT1a by ETO in neutrophils affects their migration in response to infected macrophages, we conducted a transwell chemotaxis assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that inhibiting fatty acid metabolism in neutrophils through CPT1a mediates an impact on neutrophil chemotaxis [39]. To investigate whether the inhibition of CPT1a by ETO in neutrophils affects their migration in response to infected macrophages, we conducted a transwell chemotaxis assay.…”
Section: Resultsmentioning
confidence: 99%
“…Acetyl-CoA is also generated from long-chain fatty acids via mitochondrial β-oxidation (FAO) [ 53 ] . Carbon labeling experiments have demonstrated that FAO is active in neutrophils, contributes substrate to the TCA cycle, and is reduced by neutrophil activation by lipopolysaccharide (LPS) [ 34 , 54 ] . In addition, the iterative process of FAO generates NADH and FADH 2 , which may transfer electrons directly to the ETC [ 53 ] .…”
Section: Neutrophil Metabolismmentioning
confidence: 99%
“…In addition, the iterative process of FAO generates NADH and FADH 2 , which may transfer electrons directly to the ETC [ 53 ] . FAO contributes to maintenance of the mitochondrial membrane potential as inhibition of FAO has been demonstrated to reduce the membrane potential [ 54 ] . Glutamine metabolism through glutaminolysis produces α-ketoglutarate, an intermediate in the TCA cycle [ 43 ] .…”
Section: Neutrophil Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). Recently, a Cpt1a variant with reduced enzymatic activity has been identified in humans and linked to susceptibility to various infections, including S. aureus [ 161 ]. Cpt1a inhibition with etomoxir increased bacterial burden in a mouse model of S. aureus pneumonia ( Fig.…”
Section: Significance Of Lipid Metabolism In Host Immunity To ...mentioning
confidence: 99%